PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VA SD NEGERI 29 PEKANBARU - Juwika, Dendi; Syahrilfuddin, Syahrilfuddin; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was carried out because of the low learning outcomes of social studies of grade VA in SD Negeri 29 Pekanbaru. KKM (success criteria) assigned in school that is 75, the class consist of 37 students grade VA who reached the KKM is 19 students (51,36%) and students who have not yet reached the KKM is 18 students (48,64%) with average rating of class 68,37. The purpose of this research is to improve the learning achievement of social studies of grade VA in SD Negeri 29 Pekanbaru with the application of the Two Stay Two Stray (TSTS) model. The result of this research shows that the average value of basic score is 68,37 an increased in cycle 1 become 75,67. In cycle 2 the average value increased become 84,18. The activity of the teacher on the first meeting of the cycle 1 got was 58,33% with the less category. The second meeting was 66,66% with the enough category. On the first meeting of the cycle 2 teacher activity increased become 87,50% with the very good category, at the second meeting become 95,83 % with the very good category. The activity of the students on the first meeting of the cycle 1 got was 58,33% with the less category. The second meeting was 70,83 % with the enough category. At the first meeting of the cycle 2 activity of students was 87,50 % with the very good category and the second meeting was 91,66% with the very good category. From this research it can be concluded that application of cooperative learning type Two Stay Two Stay (TSTS) model can be improve students learning outcomes of social studies of grade VA SD Negeri 29 PekanbaruKeywords: Two Stay Two Stay (TSTS), social studies outcomes